2019
DOI: 10.1186/s12951-019-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

pH and redox dual-responsive nanoparticles based on disulfide-containing poly(β-amino ester) for combining chemotherapy and COX-2 inhibitor to overcome drug resistance in breast cancer

Abstract: Background Multidrug resistance (MDR) generally leads to breast cancer treatment failure. The most common mechanism of MDR is the overexpression of ATP-binding cassette (ABC) efflux transporters such as P-glycoprotein (P-gp) that reduce the intracellular accumulation of various chemotherapeutic agents. Celecoxib (CXB), a selective COX-2 inhibitor, can dramatically enhance the cytotoxicity of doxorubicin (DOX) in breast cancer cells overexpressing P-gp. Thus it can be seen that the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…As COX-2 has been shown to be involved in P-gp-mediated multidrug resistance in cancer, a selective COX-2 inhibitor can down-regulate the P-gp expression (Sui et al, 2011). Indeed, a recent study conducted by Zhang S. et al (2019) confirmed that co-delivery of COX-2 inhibitors and doxorubicin by NPs reversed the multidrug resistance of breast cancer cells. Furthermore, several studies have revealed that codelivery of P-gp-targeted siRNA and anticancer drugs by NPs helps overcome drug-resistant cancers, which is exerted through inhibiting the expression of ABC transporters (Patil et al, 2010;Navarro et al, 2012).…”
Section: Targeting Efflux Transportersmentioning
confidence: 98%
See 1 more Smart Citation
“…As COX-2 has been shown to be involved in P-gp-mediated multidrug resistance in cancer, a selective COX-2 inhibitor can down-regulate the P-gp expression (Sui et al, 2011). Indeed, a recent study conducted by Zhang S. et al (2019) confirmed that co-delivery of COX-2 inhibitors and doxorubicin by NPs reversed the multidrug resistance of breast cancer cells. Furthermore, several studies have revealed that codelivery of P-gp-targeted siRNA and anticancer drugs by NPs helps overcome drug-resistant cancers, which is exerted through inhibiting the expression of ABC transporters (Patil et al, 2010;Navarro et al, 2012).…”
Section: Targeting Efflux Transportersmentioning
confidence: 98%
“…Efflux transporters Bypass efflux transporters NP itself (Murakami et al, 2011) Inhibit efflux transporters COX-2 inhibitors (Zhang S. et al, 2019) P-gp-targeted siRNA (Patil et al, 2010;Navarro et al, 2012) miRNA-495 (He et al, 2019) Apoptosis Inhibit anti-apoptosis pathway Bcl-2-targeted siRNA (Wang et al, 2006;Saad et al, 2008;Chen et al, 2009;Choi et al, 2019) NF-κB inhibitors (pyrrolidine dithiocarbamate/curcumin) (Fan et al, 2010;Misra and Sahoo, 2011;Zhao et al, 2019) Activate pro-apoptosis pathway Ceramide (Devalapally et al, 2007;van Vlerken et al, 2010) p53 gene therapy (Prabha and Labhasetwar, 2004;Choi et al, 2008) Efflux transporters and apoptosis…”
Section: Drugs Referencesmentioning
confidence: 99%
“…Monotherapy and combinatory therapy with COX inhibitors have been reported in the treatment of various types of cancers. Cell cycle progression, migration, invasion, angiogenesis, autophagy, apoptosis, and resistance can be classified as biochemical events that are vulnerable to either direct or indirect actions of COX inhibitors [ 4 , 5 , 6 , 7 , 8 ]. While COX inhibitors appear to induce adverse effects and off-target actions, they also display chemo-preventive properties that warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid based nanoparticles were synthesized for loading multi drug resistance (MDR) blocking drug (Cyclooxygenase 2) and doxorubicin to treat against MDR resistant tumor. This nanoparticle contain core of sPBAE, PLGA Cyclooxygenase 2 (CXB) and doxorubicin (Zhang S. et al, 2019).…”
Section: Multistimuli-responsive Systemsmentioning
confidence: 99%